Les présidents de la Commission européenne: entre trajectoires professionnelles et circonstances politiques - Victor Negrescu (Romanian Journal of European Affairs, 2012)
The important impact of the international economic crisis on the national European economies led to the strengthening of the role of the European Commission and of its president who started to play a double role by preserving the bureaucratic image while dynamically acting as a spokesman for the European austerity measures. This situation confirms the importance of the personality of the European leaders on the role they play at European level, therefore it would be important for us to study the social and professional background of the EC presidents to understand their role in the European Union's evolution. This research will enable EU specialists to render more important the social dimension of their studies and appreciations on different policy-making styles.